Anti-quorum Sensing and Protective Efficacies of Naringin Against Aeromonas hydrophila Infection in Danio rerio - Srinivasan, Ramanathan; Devi, Kannan Rama; Santhakumari, Sivasubramanian; Kannappan, Arunachalam; Chen, Xiaomeng; Ravi, Arumugam Veera; Lin, Xiangmin (Frontiers in Microbiology, 2020)
It is now well known that quorum sensing (QS) mechanism coordinates the production of several virulence factors and biofilm formation in most of the pathogenic microorganism. Aeromonas hydrophila is a prime pathogen responsible for causing frequent outbreaks in aquaculture settings. Recent studies are also continuously reporting that A. hydrophila regulates virulence factors production and biofilm formation through QS system. Addition to the presence of antibiotic resistance genes, biofilm mediated antibiotic resistance induces the severity of A. hydrophila infections. To control the bacterial pathogenesis and subsequent infections, targeting QS mechanism has become one of the attractive and best alternative methods. Though a very few compounds were identified as QS inhibitors against A. hydrophila, till date, the screening and identification of new and effective natural QS inhibitors is at the dire need to control the infectious A. hydrophila. The present study endorses the naringin (NA) as an anti-QS and anti-infective agent against A. hydrophila. Initially, the NA showed a concentration-dependent biofilm reduction against A. hydrophila. Further, the results of microscopic analyses and quantitative virulence assays displayed the promises of NA as a potential anti-QS agent. Subsequently, the down-regulation of ahh1, aerA, lip and ahyB validate the interference of NA in virulence gene expression. Further, the in vivo assays were carried out in zebrafish model system to evaluate the anti-infective potential of NA. The outcome of the immersion challenge assay showed that the recovery rate of the zebrafish has substantially increased upon the treatment with NA. Furthermore, the quantification of the bacterial load upon NA treatment showed a decreased level of bacterial counts in zebrafish when compared to the untreated control. More, the NA treatment averts the pathogen-induced histoarchitecture damages in vital organs of zebrafish, compared to their respective controls. Thus, the current study divulged the anti-QS and anti-infective capabilities of NA and could be employed to formulate effective treatment measures against A. hydrophila infections.